Use and safety of antiepileptic drugs in psychiatric inpatients-data from the AMSP study - Druschky, Katrin; Bleich, Stefan; Grohmann, Renate; Engel, Rolf R.; Kleimann, Alexandra; Stuebner, Susanne; Greil, Waldemar; Toto, Sermin (European archives of psychiatry and clinical neuroscience, 2018)
The psychiatric utilization patterns and risks of antiepileptic drugs (AEDs) were assessed by using data from the drug safety programme Arzneimittelsicherheit in der Psychiatrie over the time period 1993-2013. In a total of 432,215 patients, the main indications for AED use were acute mania, schizoaffective disorder, and schizophrenic and organic psychoses. Valproic acid (VPA) was the most common substance across all of those groups, reaching administration rates of up to 50% since 2005, at which time carbamazepine (CBZ) administration consistently dropped below a rate of 10%. Lamotrigine (LTG) and pregabalin (PGB) increased in relevance after 2005 and 2010, respectively (with administration rates of up to 9%), whereas oxcarbazepine (OXC) was least prevalent (<3%). The mean rates of severe adverse drug reactions (ADRs) ranged from 6 cases per 1000 patients treated (VPA) to 19/1000 (OXC) and were significantly lower with treatment with VPA compared to OXC and CBZ. Hyponatremia was the leading ADR during treatment with OXC; severe allergic skin reactions were most often observed during treatment with CBZ and LTG, and severe oedema was most common during treatment with PGB. Severe hyponatremia induced by OXC was observed significantly more often in female patients than in male patients.
EVALuna2:36358